A systematic literature review on environmental sustainability issues of flexible packaging: potential pathways for academic research and managerial practice - Farrukh A; Mathrani S; Sajjad A (MDPI (Basel, Switzerland), 2022)
The purpose of this review is to investigate environmental sustainability issues of the flexible packaging (FP) segment of the packaging industry. Increasingly, waste and pollution caused by FP have become a significant challenge for global sustainable development. Prior research studies have examined a diverse set of environmental challenges associated with FP, albeit, in a fragmented way. There is a paucity of research exploring and synthesizing the environmental burden of FP in an integrated fashion. To bridge this knowledge gap, we conducted a systematic literature review (SLR) to identify, synthesize, and analyze the environmental sustainability issues of FP utilizing the SCOPUS database. Based on an in-depth critical analysis of selected articles, this paper provides novel insights to scholars, practitioners, and policymakers for developing an improved understanding of environmental issues of the FP sector. This paper promotes academic scholarship and strengthens managerial practice in addressing the environmental sustainability challenges of FP.
Keywords: environmental issues; sustainable development; flexible packaging; plastic waste; recycling